ANALISIS SENSORI RUSIP DARI SUNGAILIAT-BANGKA - Koesoemawardani, Dyah (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2007)
The objective of this work was to analyze the sensory properties of rusip from traditional market in Sungailiat-Bangka. Purposed sampling was used to collect the samples, and sensory analysis was done by using free choice profiling (FCP) and focus groups method. The Results shows that sensory properties of raw rusip were opaq, thick, and partly mashy.. The colors were grey, brown and very dark brown. The dominant taste were salty, sour, bitter, and the sensation to the tongue was burned and ichy. The aromas formed were fishy, acidic, and rotten. In addition it was also noticed terasi and sardine-like aromas. Keyword : rusip, Bangka, sensory, free choice profiling, focus groups